IMPLEMENTASI SISTEM APLIKASI GOESSTI (GOOGLE SPREADSHEETS INTERNAL) BARANG PERSEDIAAN DALAM PENYUSUNAN LAPORAN KEUANGAN YANG AKUNTABEL (Studi Kasus pada Badan Perencanaan Pembangunan Daerah Kota Semarang) - Puspasari, Gusti Ayu Dewi; Santosa, Agus Budi (Jurnal Riptek, 2025)
This study aims to analyze the implementation of GOESSTI (Google Spreadsheets Internal) application in inventory management to support accountable financial reporting at the Regional Development Planning Agency (Bappeda) of Semarang City, and more broadly, to support the preparation of accountable financial statements at the Semarang City Government level. The study employs a qualitative research design with an inductive descriptive approach, with data collection through documentation, observation, and in-depth interviews with 11 informants including the Head of Bappeda, Division Heads as Budget Users, and Inventory Managers. Analysis of the data used in this study employs the SWOT Matrix analysis tool. The results show that the Strengths and Weaknesses indicator (IFAS) weighting obtained was 1.17, and the total weighting score of the Opportunities and Threats (EFAS) indicator was 1.04. This positions GOESSTI in quadrant I (Growth Strategy), utilizing internal strengths to capitalize on external opportunities. The implementation of GOESSTI has successfully improved financial reporting accuracy, transparency, and accountability through standardized recording formats, real-time data integration, and comprehensive audit trails. The research recommends further system development, human resource capacity building, and potential expansion to other government agencies to optimize inventory management within the Semarang City Government environment.